MODELO DE LIDERAZGO GERENCIAL Y SU INCIDENCIA EN CALIDAD DE SERVICIOS QUE BRINDA EL PERSONAL DE SALUD DEL HOSPITAL MARTIN ICAZA DE LA CIUDAD DE BABAHOYO, DEL CANTON BABAHOYO, PROVINCIA DE LOS RIOS - JOSE OLMEDO GARNICA VARGAS (2009)
MANAGERIAL LEADERSHIP MODEL AND ITS IMPACT ON THE QUALITY OF SERVICES PROVIDED BY THE HEALTH STAFF OF THE MARTIN ICAZA HOSPITAL OF THE CITY OF BABAHOYO, OF THE BABAHOYO CANTON, PROVINCE OF LOS RIOS